A Foresight Study on the Adoption of Augmented Reality in the Entertainment Industry - Zahari, Nur Hazwani; Salim, Siti Aisyah (Research in Management of Technology and Business, 2023)
Augmented Reality (AR) is a technology that connects virtual and physical reality while music is a whole-time entertainment for Malaysians regardless of their race and cultural background. Past studies on AR and music has been introduced with Malaysia Music Augmented Reality (MMAR) for helping children have fun while learning music. Study on the usage of AR technology in the music industry needs more recognition and acceptance from citizens and professionals as the context of Malaysia is still lacking. With AR technology adoption, it will help music industry to be promoted at higher level in the future. The aim of this study is to determine the key drivers of AR adoption and future scenarios of AR adoption in Malaysia. In this study, qualitative and quantitative approaches are mixed for data collection. Foresight analysis approaches, STEEPV also used in identifying the ten merged key drivers and issues for this study. SPSS software was used for data analysis from the 116 questionnaires answered with a 38.67% response rate. The future scenarios of AR adoption have been identified by using impact-uncertainty analysis with user experiences efficiency and system work effectiveness having the highest impact and uncertainty. At the end of this study, the four proposed scenarios were user-friendly technology, sustainable development of AR, sluggish technology, and improved comfort and experience.